2024
DOI: 10.3390/plants13050588
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single Nucleotide Polymorphic Loci and Candidate Genes for Seed Germination Percentage in Okra under Salt and No-Salt Stresses by Genome-Wide Association Study

Gaowen Xu,
Yujing Cheng,
Xiaoqiu Wang
et al.

Abstract: Excessive soil salinity is a major stressor inhibiting crops’ growth, development, and yield. Seed germination is a critical stage of crop growth and development, as well as one of the most salt-sensitive stages. Salt stress has a significant inhibitory effect on seed germination. Okra is a nutritious vegetable, but its seed germination percentage (GP) is low, whether under salt stress conditions or suitable conditions. In this study, we used 180 okra accessions and conducted a genome-wide association study (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Both conventional breeding and marker-assisted breeding (MAB) approaches have been utilized to enhance yield traits in soybean crops ( Raju et al., 2018 ). Recent studies have demonstrated that MAB approaches are particularly effective for traits that are sensitive to environmental conditions, such as seed germination, seedling development, and maturity ( Saminadane et al., 2024 ; Xu et al., 2024 ). By utilizing a specially designed marker primer design program, MAB demonstrates significant potential in molecular breeding, offering a promising avenue for the development of improved crop varieties with desired traits ( Xia et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both conventional breeding and marker-assisted breeding (MAB) approaches have been utilized to enhance yield traits in soybean crops ( Raju et al., 2018 ). Recent studies have demonstrated that MAB approaches are particularly effective for traits that are sensitive to environmental conditions, such as seed germination, seedling development, and maturity ( Saminadane et al., 2024 ; Xu et al., 2024 ). By utilizing a specially designed marker primer design program, MAB demonstrates significant potential in molecular breeding, offering a promising avenue for the development of improved crop varieties with desired traits ( Xia et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%